2005
DOI: 10.1002/pssb.200441121
|View full text |Cite
|
Sign up to set email alerts
|

How do electronic properties of conventional III–V semiconductors hold for the III–V boron bismuth BBi compound?

Abstract: We have performed ab-initio self-consistent calculations using the full potential linear augmented plane wave method to investigate the structural and the electronic properties of the boron bismuth III -V compound BBi. Our calculations provide the first available information about the structural and electronic ground-state properties of BBi. Total energy calculations of the cubic zinc-blende, wurtzite, rock-salt, cesium chloride and orthorhombic Cmcm phases are made. The zinc-blende structure is found to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
(24 reference statements)
4
21
0
Order By: Relevance
“…For phonon properties, it is found that the born effective charge and LO-TO splitting of BBi increase with rising pressure. Furthermore, the ZB structure phase is the ground state of BBi and the band structure of BBi shows unique features like a strong p-p mixing of the VBM using WIEN2k code [76]. The calculated charge density shows an anomalous behavior, characterized by a charge transfer towards the "cation" B atom.…”
Section: Electronic and Optical Properties Iii-bi Compoundmentioning
confidence: 99%
“…For phonon properties, it is found that the born effective charge and LO-TO splitting of BBi increase with rising pressure. Furthermore, the ZB structure phase is the ground state of BBi and the band structure of BBi shows unique features like a strong p-p mixing of the VBM using WIEN2k code [76]. The calculated charge density shows an anomalous behavior, characterized by a charge transfer towards the "cation" B atom.…”
Section: Electronic and Optical Properties Iii-bi Compoundmentioning
confidence: 99%
“…Some important remarkable differences between the physical properties of conventional III-V and the heavier bismuth III-V compounds were noticed recently in the work of Zaoui et al [2]. The electronic behavior of Boron-bismuth (BBi) in its zincblende phase was studied by Madouri et al [3], using the full potential linearized augmented plane wave (FPLAPW) method and as implemented in the WIEN2k code [4]. Under hydrostatic pressure, the low pressure phase of crystalline material is destabilized and structural phase transition occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The values of the lattice parameter a 0 , bulk modulus B 0, and its pressure derivative B 0 ′ of both zincblende and Rock-salt phases are presented in table.1, and compared with the available theoretical data [1], [2], [3], [5], [6], [8], [16], [17]. It is seen that, our calculated lattice parameter a 0 of both zincblende and Rock-salt phases are in general in good agreement with the other theoretical data [1], [2], [3], [5], [6], [8], [16], and [17].…”
Section: Geometry Optimizationmentioning
confidence: 99%
“…In fact, they mentioned that the obtained values of the indirect band-gap energy decrease with increasing of hydrostatic pressure. Using the full potential linearized augmented plane wave method, and as implemented in the WIEN2k code, the electronic behavior of BBi material was also studied by Madouri et al [3]. They found that this material is a semiconductor with direct band-gap with a small optical transition of about 0.13 eV.…”
Section: Introductionmentioning
confidence: 99%